Enhancing Students' Critical Thinking in Thermodynamics through Long Bumbung Local Wisdom-Based Physics Comics - Erlangga, Sony Yunior; Setyawan, Dhimas Nur; Wijayanti, Astuti; winingsih, puji hariati; Poort, Elang Amadious (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2024)
This study aims to develop and assess the impact of the Long Bumbung comic, based on local wisdom, in enhancing critical thinking skills in thermodynamics. The research used a quasi-experimental method with 120 students across six eleventh-grade classes of SMA Sahabatqu Yogyakarta. The researchers randomly selected two classes of 60 students each for the intervention. The research employed the Research and Development method with the 4D model. The results showed that the Long Bumbung comic was highly feasible, with positive feedback from experts on its material, learning, and language aspects. Critical thinking skills improved more in the experimental group, with an N-gain of 0.64 compared to 0.53 in the control group. Student interest was notably high, with 83.33% expressing enthusiasm for the comic. This finding underscores the comic's effectiveness and appeal as a culturally relevant educational tool, enhancing critical thinking and engagement